Phosphorus Stock Depletion and Soil C:N:P Stoichiometry Under Annual Crop Rotations and Grassland Management Systems Over 13 Years - Somavilla, André; Caner, Laurent; da Silva, Isley Cristiellem Bicalho; Rheinheimer, Danilo dos Santos; Chabbi, Abad (Frontiers in Soil Science, 2022)
Phosphorus (P) nutrition is essential to both plant yield and soil organic matter (SOM) input. However, continuous extraction of P by plants and biomass harvesting can lead to soil P stock depletion, a reduction in crop yields and ultimately a reduction in organic matter input to the soil. In this work, we analysed P, C and N stock trends in the 0-30 cm topsoil layer cultivated with permanent cropland (CC) and mowed permanent grassland (GG) for 13 years. In addition, we characterized the changes in P organic forms by using 31P-NMR. The results showed that the amount of P exported within 13 years was 10% greater in GG than in CC (295 and 268 kg ha-1, respectively). The total P stocks decreased under both the CC and GG management systems (0.30 and 0.25 Mg ha-1, respectively). This depletion was mainly observed in total Pi forms, which recorded reductions of 0.75 and 0.29 Mg ha-1 in GG and CC, respectively. The total Po stock increased by 42.6% in GG; these results were consistent with the increase in C and N stocks in GG (2.6 and 0.19 Mg ha-1, respectively) and their reduction in CC (-4.2 and -0.38 Mg ha-1, respectively). Although P depletion mainly affected the P pool presenting the highest lability (labile P), this depletion did not have a negative effect on plant yield after 13 years due to the buffering capacity of P pools presenting less lability (moderately labile P). Mowing permanent grasslands led to a change in the pool of labile P from inorganic to organic forms and an increase in soil C and N stocks. Based on the 31P-NMR technique, permanent grasslands significantly reduced α-glycerophosphate and increased myo-IHP and adenosine monophosphate more than the permanent cropland. Although there was no significant decrease in productivity, the depletion of available P should be monitored over time, especially in mown permanent grassland crops, to prevent potential nutrient stress.